Influence of quenching temperature from the intercritical interval on the character of X70 steel strain hardening - V. G. Gavrylova; N. E. Mak-Mak; M. A. Grigoreva (Журнал інженерних наук)
The article presents the analysis of the diagrams of X70 steel tension, previously normalized and quenched in water from intercritical А1-А3 interval, there were calculated the degree of hardening, evenly elongation and hardening coefficient as the ratio of the difference between the tensile strength and yield strength to the elongation of samples on the diagram tension sector, that corresponds to the evenly elongation. The nature of strain hardening coefficient  * change is determined. Its value becomes  1,8 times higher with the raising of quenching temperature of intercritical interval. Herewith the mixed ferritic– martensitic structure is formed, which dispersion increases with the raising of heating temperature for hardening of the mentioned interval. The results are recommended to use in the development of thermal hardening modes of low-carbon and low-alloy steels, as well as in the evaluating the parameters of their technological and functional characteristics.